The City of the Absent and the Over-Present. About Ręka pszczelarza (The Beekeeper’s Hand) by Tomasz Różycki in the Context of Benjamin’s Theory of Wandering - Śniedziewska, Magdalena (Porównania, 2025)
In my article, I attempt to interpret Ręka pszczelarza (The Beekeeper’s Hand), a poetry collection by Tomasz Różycki published in 2022. I focus on two types of encounters with others, which Różycki poetically recounts. The first are imaginative and made possible through the work of memory and the lyrical subject’s particular sensitivity; the second, real, are embedded in the slowed-down rhythm of pandemic reality. In my article, I examine dialogues with both the absent and the overpresent. I refer to as absent those figures associated with the history of Berlin (mostly victims of the Holocaust, though not exclusively). The overpresent, on the other hand, are inhabitants of various kinds of social margins – hence the prefix over-, indicating their excessiveness or even unwanted presence. To describe Różycki’s creative method, I draw on Walter Benjamin’s theory of flânerie and a particular form of melancholy known as kutabuk. I argue that Ręka pszczelarza, structured around the logic of wandering, is both a poetic labyrinth and a melancholic lament for all forms of humanity that Różycki seeks to preserve.